(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reconfigurable antennas have the great utility in smart and adaptive. The reconfigurable characteristic offer many advantages in wireless applications such as fourth generation (4G) and fifth generation (5G) mobile terminals. A reconfigurable antenna needs to have an adequate number of active elements for the reconfiguration of antenna characteristics. These high-quality active elements increase the cost and biasing complexity of the networks to control the circuitry. The current distribution in the radiating patch is responsible of antenna’s characteristics, which can be change through changing the current flow in the patch. To change the current distribution in radiating patch the active element (switches) are required such as MEMS switch, varactor diode and p-i-n diodes. Therefore, we have presented a review on the reconfigurable antennas for advance wireless terminals, which are recently proposed by the other authors.